Democratisation in Nigeria: Problems and Future Prospects - Wani, Hilal Ahmad; Suwirta, Andi (SOSIOHUMANIKA, 2013)
ABSTRACT: Nigeria, as a major democracy in African continent, has to respect every faith, culture, community, language, and every identity which exists in Nigeria. There is immense need that government should manage all the gap and gulf between the different communities through working properly for the greater interest of all the citizens, without any differentiation and distinction. Those who are oppressed sections of this society, the greater attention is required for their betterment. All developing countries are in transition, and Nigeria is not different case from other developing countries. In summation, it can be said that democratic governance and accountable political system is needed to fulfil the vacuum. Democratic system of governance could be the real panacea of all the problems which country is facing. This paper is an attempt to understand the process of democratisation in Nigeria. Democratisation term will elucidate that whether the government is successful in promoting and maintaining justice and rule of law or whether the government is not successful in the process of democratisation. This study will also touch all the lacunas of democracy in Nigeria. The main discourse is that government has to understand the real problems of people in any democratic country and try to fulfil all the basic amenities and entitlements for its citizens. KEY WORD: Nigeria government, process of democratisation, rule of law, happy and prosperous country, and accountable and good governance.Â RESUME: Artikel ini berjudul âDemokratisasi di Nigeria: Masalah dan Prospek Masa Depanâ. Nigeria, sebagai negara demokrasi besar di benua Afrika, harus menghormati setiap agama, budaya, masyarakat, bahasa, dan setiap identitas yang ada di Nigeria. Ada kebutuhan mendesak bahwa pemerintah harus mengelola semua kesenjangan dan jurang antara masyarakat yang berbeda melalui program kerja yang baik untuk kepentingan yang lebih besar dari semua warga negara, tanpa perbedaan dan pemisahan. Mereka yang tertindas dalam masyarakat memerlukan perhatian yang lebih besar untuk kemajuan mereka. Semua negara-negara berkembang berada dalam masa transisi, dan Nigeria bukan kasus yang berbeda dari negara-negara berkembang lainnya. Dalam perkiraan dapat dikatakan bahwa pemerintahan yang demokratis dan sistem politik yang akuntabel diperlukan untuk memenuhi kevakuman. Sistem pemerintahan yang demokratis bisa menjadi obat mujarab nyata bagi semua masalah yang dihadapi oleh negara. Makalah ini merupakan upaya untuk memahami proses demokratisasi di Nigeria. Istilah demokratisasi akan menjelaskan bahwa apakah pemerintah berhasil dalam mempromosikan dan mempertahankan keadilan dan supremasi hukum atau apakah pemerintah tidak berhasil dalam proses demokratisasi itu. Penelitian ini juga akan menyentuh semua kehampaan demokrasi di Nigeria. Wacana utama adalah bahwa pemerintah harus memahami masalah nyata dari rakyatnya di setiap negara yang demokratis serta mencoba untuk memenuhi semua kebutuhan dasar dan hak dari warga negaranya.KATA KUNCI: Pemerintah Nigeria, proses demokratisasi, supremasi hukum, negara bahagia dan sejahtera, serta akuntabilitas dan pemerintahan yang baik.Â Â About the Authors: Dr. Hilal Ahmad Wani is a Research Fellow at the Centre for Civilizational Dialogue UM (University of Malaya) in Kuala Lumpur, Malaysia; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Department of History Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia. Corresponding authors are: wanihilal@gmail.com and atriwusidna@gmail.comHow to cite this article? Wani, Hilal Ahmad & Andi Suwirta. (2013). âDemocratisation in Nigeria: Problems and Future Prospectsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.2 [November], pp.143-158. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 6, 2013); Revised (October 9, 2013); and Published (November 20, 2013). Â  Â